SYNTHESIS AND CONFORMATIONS OF p-(ACETAMIDO)-BUTOXYCALIX[4]ARENE AND p-(BENZAMIDO)-BUTOXYCALIX[4]ARENE - Firdaus Firdaus; Jumina Jumina; Hardjono Sastrohamidjojo (Indonesian Journal of Chemistry, 2007)
The conversion of p-(amino)butoxycalix[4]arene, 1, to p-(acetamido)butoxy-calix[4]arene, 2, and p-(benzamido)butoxycalix[4]arene, 3, via acetylation and benzoylation reactions, respectively have been conducted. The acetylation reactions was conducted by reflux method and room temperature method. The reflux method was conducted by refluxed a solution of 1 and acetic anhydride in acetic acid glacial solvent for 12 hours to result 2 in 53.8% yield; while the room temperature method was conducted by stirred a solution of 1, acetyl chloride, and dry pyridine in dry toluene solvent and inert atmosphere at room temperature for 24 hours to result 2 in 97.8% yield. By the room temperature method and using benzoyl chloride, the compound 3 was obtained in 67.1% yield. Structures of the both compounds were confirmed using IR, 1H NMR, and 13C NMR spectroscopy methods. Pursuant to the 1H-NMR spectral patterns of their bridge methylene and calix aryl protons, they were known that the compound 3 exist in partial cone conformation; whereas the compound 2 exist in partial cone, cone, and 1,2-alternate conformations where the partial cone was the main conformer.